SOME HYDROBIOLOGICAL CHARACTERISTICS OF THE SURF REGION OF WEST HILL, CALICUT - Lalmohan, R S (Indian Journal of Fisheries, 2011)
The note presents some hydrobiological characters of the surf waters ofCalicut for the three years 1975-78, with special emphasis on the postlarval fishand prawns.